2018
DOI: 10.1002/hep.29815
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor signaling activates the hepatic X‐box binding protein 1 pathway in vitro and in mice

Abstract: FXR signaling activates the IRE1α/XBP1 pathway in vivo and in vitro. FXR pathway activation increases XBP1 splicing and enhances p-IRE1α expression. These effects are mediated, at least in part, by SHP. IRE1α/XBP1 pathway activation by bile acids and pharmacological FXR agonists may be protective during liver injury and may have therapeutic implications for liver diseases. (Hepatology 2018;68:304-316).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…Furthermore, several studies have demonstrated amelioration of maladaptive ER signalling via FXR agonism in the kidney (Gai et al, ; Marquardt et al, ). These observations support the notion that FXR agonism may be involved in hepatic ER stress alleviation, although a recent study indicated that FXR activation induces hepatic ER stress via targeting XBP1/IRE1α signalling (Liu et al, ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, several studies have demonstrated amelioration of maladaptive ER signalling via FXR agonism in the kidney (Gai et al, ; Marquardt et al, ). These observations support the notion that FXR agonism may be involved in hepatic ER stress alleviation, although a recent study indicated that FXR activation induces hepatic ER stress via targeting XBP1/IRE1α signalling (Liu et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…These findings suggest that FXR activation could reduce hepatic ER stress, and this effect may be involved in the anti‐NAFLD effect of FXR agonists. In contrast, in a recent article it was suggested that hepatic FXR activation exacerbates ER stress (Liu et al, ). Thus, the role of hepatic FXR activation in regulating the ER stress process remains to be clarified.…”
Section: Introductionmentioning
confidence: 92%
“…A recent report suggests that FXR signaling modulates ER stress via activation of the IRE/XBP1 pathway (11). Our findings show that mice lacking FXR resulted in reduced expression of GRP94, ATF4, EDEM, XBP1 (including total, spliced and unconventional spliced XBP1) in the liver when suffering from IRI, suggesting that the absence of FXR forfeits protection of hepatocytes from apoptosis, contributing to the susceptibility to liver IRI.…”
Section: Discussionsupporting
confidence: 55%
“…Activation of the BA membrane receptor, G protein-coupled BA receptor 1 (TGR5), by TGR5 agonists inhibits inflammatory responses and attenuates liver IRI by suppressing the Toll like receptor 4 (TLR4)-NF-B mediated pathway (10). Recent experimental data suggest that activation of BA nuclear receptor, farnesoid X receptor (FXR), stimulates the IRE/XBP1 pathway and may be protective during liver injury (11). Similarly, administration of the FXR-agonist obeticholic acid (OCA) improves survival in a rodent model of intestinal IRI, through gut barrier preservation and mitigated inflammation (12).…”
Section: Introductionmentioning
confidence: 99%
“…A potential additional level of complexity arose from a recent study showing that FXR can activate the IRE/XBP1 pathway . That study notably suggests a role for FXR in XBP1 activation in the early stages of cholestasis, using a mouse bile duct ligation model.…”
Section: Discussionmentioning
confidence: 99%